A research-driven flowchart to approach change in couples - Francesca Capozzi (Frontiers in Psychology)
In most cases, couple therapists systemically see couples’ distress as the result of reciprocal maladaptive patterns to which each partner contributes. Yet, therapists can struggle to share with the couple such a relational understanding of their distress and identify goals for change accordingly, as structured, step-by-step methods are not available in the extant literature. This perspective paper reviews research across various domains of relationship science to summarize cohesively the best practices for goal identification in a step-by-step flowchart. The flowchart is divided into three main areas, derived from the available literature: establishing couple therapy appropriateness, determining general goals, and conceptualizing specific goals from a systemic perspective. Aimed at facilitating training, the resulting recommendations will broadly support a goal-focused approach to systemic assessment.